Determination of the spatial distribution of ship’s noise components - Bittner, P.; Kozaczka, E. (Archives of Acoustics, 2001)
The investigations of vibroacoustic activity of a ship is a topic of interest for technical diagnostics, ecological and military reasons. A ship may be treated as a coaxial sound source. Descriptions of the field distribution for such sources are common in literature. The methods used for solving the radiation problem include analytical solutions, numerical methods and experimental investigations. As a ship is a complex sound source, it is difficult to find an analytical description of its radiation in the near field region. Therefore the paper describes a method which has the elements of a numerical and an experimental one. The hull is surrounded with a surface which replaces the ship as a source. The experimentally obtained distributions of acoustic quantities were used to calculate the pressure value in any point in space outside the virtual surface. A numerical method has been worked out basing on the Helmholtz solution of the exterior radiation problem and the superposition method. It was verified by comparing its results with the approximate analytical dependence found out for a simple source of the shape similar to the virtual surface. The method of measuring the acoustic quantities is described next. The special attention was paid to the particle velocity measurements. The theoretical background was followed with the results of laboratory measurements. After the laboratory investigations, the method has been checked during in situ measurements.